2013
DOI: 10.1002/jor.22486
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain‐related behavior and pro‐inflammatory cytokine levels in the rat rotator cuff tear model

Abstract: The cause of pain following rotator cuff tear has not been fully elucidated. The purpose of this study was to evaluate behavior and inflammatory cytokines in a rat unstabilized rotator cuff defect (UCD) model. Forty-five Sprague-Dawley rats were divided into three groups: sham; UCD; and stabilized rotator cuff defect (SCD). Gait analysis was examined using CatWalk. Tumor necrosis factor (TNF)-a, interleukin(IL)-1b, and IL-6 were measured within the subacromial bursa and the glenohumeral joint synovium at 21 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…Second, hip pain was suggested by immunohistochemical determination of CGRP expression. Further study is needed to determine pain-related behavior using other methods such as evaluation of weight bearing in walking animals [32][33]. Third, dose dependency could not be found, since only NGF50 and NGF100 groups were documented.…”
Section: Discussionmentioning
confidence: 91%
“…Second, hip pain was suggested by immunohistochemical determination of CGRP expression. Further study is needed to determine pain-related behavior using other methods such as evaluation of weight bearing in walking animals [32][33]. Third, dose dependency could not be found, since only NGF50 and NGF100 groups were documented.…”
Section: Discussionmentioning
confidence: 91%
“…Pain‐related behavior is useful to evaluate pain in animal models. Gait disturbance is widely accepted as a pain‐related behavior . However, gait disturbance has not been examined in a rat model of hip OA induced by MIA.…”
mentioning
confidence: 99%
“…Therefore, rats were considered to be a suitable animal for the development of a RCT experimental model. However, few studies have evaluated pain relief in an animal RCT model, and there are currently few systems capable of quantifying rat forelimb function …”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki et al reported that rotator cuff repair not only improved shoulder function, but also reduced inflammatory cytokines. In addition, they also showed that suppression of inflammation improved shoulder function.…”
Section: Discussionmentioning
confidence: 99%